2020
DOI: 10.1097/psy.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Resting Total Peripheral Resistance: A Systematic Review and Meta-Analysis

Abstract: Objective Decades of research suggest that there may be important ethnic differences in the hemodynamic mechanisms that co-determine arterial blood pressure, the primary diagnostic index of hypertension. In general, studies have observed that, compared with European Americans (EAs), African Americans (AAs) exhibit higher total peripheral resistance (TPR), an important summative index of peripheral vascular constriction. In contrast, EAs have been reliably shown to exhibit greater cardiac output (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…The aim of this study was to preliminarily investigate whether the dysfunctional physiological profile found in African Americans is seen also in other minority groups subjected to discrimination, such as LGB. First, study 1 replicated previous reports on the presence of a so-called Cardiovascular Conundrum in African Americans, that is a pattern of high resting HRV coupled with high TPR, that is likely due to a dysfunction at the baroreflex level ( Hill et al, 2015 for a meta-analysis of ethnic differences in HRV and Brownlow et al, 2020 for a meta-analysis on ethnic differences in TPR). Study 1 did not include a stressor because the Conundrum was originally found at rest, however, the fact that resting high HRV is also associated with a more prominent vascular hemodynamic reactivity to physical (i.e., orthostasis) and emotional (i.e., anger recall) stressors in African Americans has been previously reported ( Carnevali et al, 2019 ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The aim of this study was to preliminarily investigate whether the dysfunctional physiological profile found in African Americans is seen also in other minority groups subjected to discrimination, such as LGB. First, study 1 replicated previous reports on the presence of a so-called Cardiovascular Conundrum in African Americans, that is a pattern of high resting HRV coupled with high TPR, that is likely due to a dysfunction at the baroreflex level ( Hill et al, 2015 for a meta-analysis of ethnic differences in HRV and Brownlow et al, 2020 for a meta-analysis on ethnic differences in TPR). Study 1 did not include a stressor because the Conundrum was originally found at rest, however, the fact that resting high HRV is also associated with a more prominent vascular hemodynamic reactivity to physical (i.e., orthostasis) and emotional (i.e., anger recall) stressors in African Americans has been previously reported ( Carnevali et al, 2019 ).…”
Section: Discussionsupporting
confidence: 72%
“…RMSSD was natural log-transformed to fit assumptions of linear analyses. Given extensive literature and meta-analyses (e.g., Hill et al, 2015 ; Brownlow et al, 2020 ) on baseline physiological differences between AAs and EAs, all tests were one-tailed and significance levels were evaluated using an alpha of 0.05. Effect sizes are reported as Cohen’s d.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, to produce the same degree of vasodilation, greater doses of acetylcholine are needed in AAs compared to EAs (Jones et al., 1999). Further evidence for impaired vasodilation in AAs comes from the recently identified evidence of greater vagally mediated heart rate variability (HRV), a mechanism that should be associated with reduced TPR via the baroreflex, in the presence of elevated BP (Brownlow et al, 2020; Dorr et al, 2007; Hill et al, 2015). That is, in response to a BP increase baroreceptors enhance the vagal activity and inhibit the sympathetic activity via concomitant nucleus tractus solitarii (NTS) projections to the nucleus ambiguous (NA: to increase vagal activity) and to the caudal ventrolateral medulla (CVLM: to inhibit sympathetic activity) (Hesse et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, young Black adults have been found to have an increased degree of vasoconstriction in response to a given increase in sympathetic activation. Black adults have greater vasoconstriction in response to infusion of the α 1 ‐adrenergic agonist, phenylephrine (Adefurin et al., 2013; Sherwood & Hinderliter, 1993; Stein et al., 2000), or in response to spontaneous bursts of muscle sympathetic activity, that is, neurovascular transduction (Vranish et al., 2018), that contributes to an increased pressor response to stress by inducing greater peripheral vascular constriction (Brownlow et al., 2020; Okada et al., 2016; Stein et al., 2000; Vranish et al., 2018). In addition, previous evidence has shown that Black individuals have exaggerated BP responses, during short acute sympathetic stimulation (<10 min) induced by the cold pressor test, intravenous administration of α‐adrenergic receptor agonists (Adefurin et al., 2013; Stein et al., 2000) or a video game (Murphy et al., 1986, 1994) although some reported no racial difference in BP response to different types of psychological stress (McAdoo et al., 1990).…”
Section: Introductionmentioning
confidence: 99%